Yellow Fever outbreaks in unvaccinated populations, Brazil, 2008-2009. - Alessandro Pecego Martins Romano; Zouraide Guerra Antunes Costa; Daniel Garkauskas Ramos; Maria Auxiliadora Andrade; Valéria de Sá Jayme; Marco Antônio Barreto de Almeida; Kátia Campomar Vettorello; Melissa Mascheretti; Brendan Flannery (Public Library of Science (PLoS), 2014)
Due to the risk of severe vaccine-associated adverse events, yellow fever vaccination in Brazil is only recommended in areas considered at risk for disease. From September 2008 through June 2009, two outbreaks of yellow fever in previously unvaccinated populations resulted in 21 confirmed cases with 9 deaths (case-fatality, 43%) in the southern state of Rio Grande do Sul and 28 cases with 11 deaths (39%) in Sao Paulo state. Epizootic deaths of non-human primates were reported before and during the outbreak. Over 5.5 million doses of yellow fever vaccine were administered in the two most affected states. Vaccine-associated adverse events were associated with six deaths due to acute viscerotropic disease (0.8 deaths per million doses administered) and 45 cases of acute neurotropic disease (5.6 per million doses administered). Yellow fever vaccine recommendations were revised to include areas in Brazil previously not considered at risk for yellow fever.